2019
DOI: 10.1177/0963689719870999
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from Bone Marrow Mesenchymal Stem Cells Inhibit Neuronal Apoptosis and Promote Motor Function Recovery via the Wnt/β-catenin Signaling Pathway

Abstract: Severe spinal cord injury (SCI) is caused by external mechanical injury, resulting in unrecoverable neurological injury. Recent studies have shown that exosomes derived from bone marrow mesenchymal stem cells (BMSCs-Exos) might be valuable paracrine molecules in the treatment of SCI. In this study, we designed SCI models in vivo and in vitro and then investigated the possible mechanism of successful repair by BMSCs-Exos. In vivo, we established one Sham group and two SCI model groups. The Basso, Beattie, Bresn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 58 publications
0
55
0
Order By: Relevance
“…Exos secreted by BMSCs were reported to mediate cell-to-cell communication, signaling pathway activation and decomposition of harmful substances, which may be involved in neuroprotective function. 29,30 MiR-enriched exosomes which are subsequently taken up by target cells could alter gene expression to exert biological functions. 31 The present study demonstrated that Exos derived from BMSCs loaded with miR-146a-5p could effectively alleviate brain injuries post ICH by reducing neuronal apoptosis, and inflammation associated with the suppression of microglial M1 polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Exos secreted by BMSCs were reported to mediate cell-to-cell communication, signaling pathway activation and decomposition of harmful substances, which may be involved in neuroprotective function. 29,30 MiR-enriched exosomes which are subsequently taken up by target cells could alter gene expression to exert biological functions. 31 The present study demonstrated that Exos derived from BMSCs loaded with miR-146a-5p could effectively alleviate brain injuries post ICH by reducing neuronal apoptosis, and inflammation associated with the suppression of microglial M1 polarization.…”
Section: Discussionmentioning
confidence: 99%
“…8 BMSC-derived exosomes (BMSC-Exos) have been used in animal models of various diseases including reduction of myocardial ischemia, promotion of skin healing, promotion damaged kidney repair and spinal nerves, and inhibition of liver vitaminization. [9][10][11] Studies have also shown that BMSC-Exos have a repairing effect on SCI, but the specific mechanism is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies that confirm this. 18 When β-catenin accumulates to a certain level, it can enter the cell nucleus directly, join TCF4/LEFS, activate downstream CD44, cMyc and cyclin D1 gene expression and transcription, and lead to abnormal cell proliferation. 19…”
Section: Discussionmentioning
confidence: 99%